1981
DOI: 10.1111/j.1755-3768.1981.tb08331.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CHANGES IN PC02 AND BODY POSITIONS ON INTRAOCULAR PRESSURE DURING GENERAL ANAESTHESIA

Abstract: Elevated arterial carbon dioxide tension, induced by the administration of CO2 via the respiratory air or by hypoventilation, entailed a gradual increase in the IOP in patients without eye diseases under general anaesthesia. A sudden cessation of CO2 administration or hyperventilation caused such a rapid, simultaneous fall in IOP to values below the initial level that the pressure variations must be of vascular nature, presumably related to changes in choroidal blood volume. The above-mentioned procedures alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
2
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 12 publications
0
45
2
1
Order By: Relevance
“…However, in that study we used an alpha-2 adrenoceptor agonist in combination with butorphanol and the patient was positioned in ventral recumbency. It is possible that patient positioning could cause these differences, as the ventral position can significantly increase IOP (Hvidberg et al 1981). Supine body position has been shown to increase IOP in humans, but Broadwater et al (2008) showed that this was not the case in conscious dogs in sternal recumbency.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, in that study we used an alpha-2 adrenoceptor agonist in combination with butorphanol and the patient was positioned in ventral recumbency. It is possible that patient positioning could cause these differences, as the ventral position can significantly increase IOP (Hvidberg et al 1981). Supine body position has been shown to increase IOP in humans, but Broadwater et al (2008) showed that this was not the case in conscious dogs in sternal recumbency.…”
Section: Discussionmentioning
confidence: 94%
“…Intraocular pressure can be influenced by patient recumbency (Hvidberg et al 1981;Broadwater et al 2008). All of the patients in the current study were positioned in lateral recumbency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatt and Gelatt (2001) informed that some anesthetic drugs that are to produce ocular hypotension can also produce ocular hypertension, secondary to respiratory depression and acidosis that sometimes occurs with prolonged general anesthesia. Hypoventilation contributes to the increase in venous blood pressure, with choroidal vasodilatation, causing an elevation in IOP (Duncalf and Weitzner, 1963;Hvidberg et al, 1981). In respiratory alkalosis, diminution of IOP occurs as a consequence of the reduction in the choroidal blood volume, diminution of blood flow to the ciliary body, inhibition of carbonic anhydrase enzyme, and decrease of filtration of the aqueous humor (Smith et al, 1981;Cunningham and Barry, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the blood volume of the choroid is in the venules of the choroid. Venular filling of choroid depends on the pressure in the orbital veins [117] . Pressure in the orbital veins can be affected by body position [117,124,125] .…”
Section: Autoregulationmentioning
confidence: 99%